An Examination of Centrifugation as a Method of Extracting an Extracellular Solution from Peas, and Its Use for the Study of Indoleacetic Acid-induced Growth - Terry, Maurice E. (1980)
A technique of centrifuging pea epicotyl sections which extracts water-soluble cell wall polysaccharides with less than 1.5% cytoplasmic contamination as revealed by malate dehydrogenase activity determinations was developed. Tests for protein, hexose, pentose, and malate dehydrogenase indicate that significant damage to the cells occurs above 3,000g. Below this force, there is little damage, as evidenced by the similar growth rates of centrifuged and noncentrifuged sections. Centrifugation at 1,000g extracts polysaccharides containing rhamnose, fucose, arabinose, xylose, mannose, galactose, and glucose. An increase in xylose and glucose, presumably xyloglucan, is induced by treating sections with indoleacetic acid. Much of the alcohol-insoluble, water-soluble polysaccharide within the wall is extractable by centrifugation, since nearly as much arabinose and xylose are extractable by centrifugation as by homogenization. The utility of this method for the study of cell wall metabolism is discussed.